Y=(-x*x)-4x+3
y=-(x^2+4x-3)
4+y=-(x^2+4x+4)+3
y+4=-(x-2)^2.) +3
-4. -4
y=-((x-2)^2)-1
Answers:
Vertex: (2,-1)
AOS:x = 2
Domain: All Real Numbers
Range:[-1,Infinity)
Answer:
1. 15
2. 8
Step-by-step explanation:
The two sequence are geometric progression GP, because they follow a constant multiple (common ratio)
The nth term of a GP is;
Tn = ar^(n-1)
Where;
a = first term
r = common ratio
For the first sequence;
The common ratio r is
r = T3/T2 = 540/90 = 6
r = 6
T2 = ar^(2-1) = ar
T2 = 90 = ar
Substituting the values of r;
90 = a × 6
a = 90/6
a = 15
First term = 15
2. The sam method applies here.
Common ratio r = T3/T2 = 128/32 = 4
r = 4
T2 = ar^(2-1) = ar
T2 = 32 = ar
Substituting the values of r;
32 = a × 4
a = 32/4
a = 8
First term = 8
Answer:
-2x-8
Step-by-step explanation:
1) Distribute:
-6/3x+-15/3-3
2) Simplify:
-2x-5-3
3) combine like terms:
-2x-8
hope this helps
Answer:
700 Feet?
Step-by-step explanation:
A rectangle has 4 sides.
2 of them are 100 ft
2 of them are 250 ft.
2x100=200
2x250=500
500 ft +200 ft=700ft
Answer:
(-4, -2)
Step-by-step explanation:
A = (-1, 2)
Add (-3, -4) to that and you get ...
A' = (-1-3, 2-4) = (-4, -2) . . . . matches the last choice
__
The translation function has the effect of moving the point left 3 and down 4. You can count grid squares on the graph to see that A' ends up at (-4, -2).